Shedding light on the connections between diet, metabolic health and food insecurity in the North - Gallais, Sophie (Université Laval, 2023)
Country food hunted, fished, and gathered from the land has been a pillar of Inuit health. They significantly contribute to the nutrition, health, and food security of Canadian Inuit communities. Despite this key role, the ongoing effects of colonization, climate change, changes in food preferences, socio-economic challenges and concerns about contaminant exposure are leading to a rapid dietary transition. As western diets become more prevalent in the Canadian Arctic, health concerns, such as cardiometabolic disease, are on the rise. Advances in technology have allowed for a better understanding of the link between dietary practices and disease. Two complex and interconnected systems, the gut microbiome and the endocannabinoidome, are heavily influenced by diet and mediate many dietary implications for health. The development of new tools and model organisms to allow a more in-depth investigation of these systems as well as identification of early molecular biomarkers that are relevant to cardiometabolic disease pathogenesis is vital. This chapter brings together a selection of results from Sentinel North program that are deepening our understanding of the positive impacts of country food on the intestinal microbiota, are discussing the links between diet and chronic diseases, are assessing the role of the gut-brain axis and the endocannabinoidome in metabolic health, and are shedding light on culturally adapted initiatives that tackle food and water security issues in collaboration with Northern communities.